Hubungan Resiliensi dan Coping Stres Terhadap Tingkat Stres Mahasiswa yang Mengikuti Program MBKM - Fildzah Malahati; Novita Agustin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to examine the relationship between stress levels, resilience, and stress coping strategies in students participating in the Merdeka Belajar Kampus Merdeka (MBKM) program. A quantitative method with a correlational approach was employed for the research. Data were collected using questionnaires that included scales for stress, resilience, and coping stress, with 100 students from Yogyakarta involved in the study. The Spearman correlation test showed a significant relationship between resilience and coping stress with stress levels, with a correlation coefficient of 0.627. However, the multiple linear regression hypothesis test revealed that resilience and coping stress did not have a significant impact on students' stress levels at the 0.001 significance level (p = 0.665). While a relationship between the variables was identified, their effect was not strong enough to be statistically significant. This study suggests the need for enhancing resilience and stress coping management to reduce stress levels among students in the MBKM program.